Relasi Gender dalam Keluarga pada Suku Hubula di Kampung Isaima Distrik Usilimo Kabupaten Jayawijaya - Ratna Mabel; Marlina Flassy; Gerdha K.I. Numberi (Universitas Cenderawasih, 2020)
This article aims to describe and analyze gender relations and the division of roles between men and women in the life of the Hubula tribe in Kampung Isaima, DIstrik Usilimo, Jayawijaya Regency. The research method used is descriptive qualitative ethnographic approach. The data collection techniques used were in-depth interviews, observation, and documentation. Data analysis includes the stages of data reduction, data display and conclusion. The results showed that there was participation in production and reproduction activities, husband and wife did the division of labor based on the consensus that they had previously discussed. However, despite the participation of men / husbands, the share of women in production and reproduction activities is still larger. Then in social activities, men take a bigger portion.